Strategi Peningkatan Keterlibatan Peserta Didik dalam Pembelajaran Ekonomi - Wahyu Syata (Educational Journal, 2026)
This research aims to identify, analyze, and synthesize various effective learning strategies to enhance student engagement in Economics education. The method used is a literature review by examining ten relevant scientific articles published between 2023 and 2025. The data used are secondary data obtained from scientific journals, books, and other academic sources. The data collection technique was carried out thru the stages of identification, selection, and grouping of literature based on topic relevance. The study results indicate that student engagement is a multidimensional construct encompassing behavioral, emotional, and cognitive aspects, and is influenced by various internal and external factors. Innovative learning strategies such as gamification, active learning, discovery learning, and project-based learning have proven capable of enhancing students' motivation, participation, and critical thinking skills. In addition, the use of appropriate learning media and the integration of digital technology also contribute to creating more engaging and meaningful learning experiences. Innovation in classroom management and the creation of adaptive, interactive, and conducive learning environments are also important factors in supporting student engagement. The findings of this research emphasize that increasing student engagement cannot be achieved thru a single approach, but rather requires a combination of integrated strategies tailored to the characteristics of the students and the learning context. This research is expected to serve as a reference for educators in developing more innovative, effective, and student-centered Economics learning practices.